Replacing Fallow with Continuous Cropping Reduces Crop Water Productivity of Semiarid Wheat. (1st January 2013) - Aiken, R. M.; O'Brien, D. M.; Olson, B. L.; Murray, L.
Abstract : Water supply frequently limits crop yield in semiarid cropping systems; water deficits can restrict yields in drought‐affected subhumid regions. In semiarid wheat ( Triticum aestivum L.)‐based cropping systems, replacing an uncropped fallow period with a crop can increase precipitation use efficiency but reduce wheat productivity. Our objective was to analyze crop sequence and environmental effects on water use, components of water productivity, and net returns of winter wheat (WW) in a semiarid region. A field study was established to evaluate eight 3‐yr crop sequences, including a wheat phase followed by a feed grain phase (corn [ Zea mays L.] or grain sorghum [ Sorghum bicolor (L.) Moench]) and an oilseed phase (OS; spring canola [ Brassica napus L.], soybean [ Glycine max (L.) Merr.], sunflower [ Helianthus annuus L.], or none [fallow]). Standard measurements included crop water use (WU), canopy leaf area index at anthesis, biomass, grain yield, and yield components. Net return (NR) was calculated as the difference between crop revenue and total operating costs. Replacing an uncropped fallow period with an OS crop reduced water productivity responses of WW (biomass, grain yield, and NR) by 18, 31, and 56%, respectively, relative to that of WW grown after fallow. These responses to continuous cropping corresponded to reductions in all components of a water‐limiting yield production function. The modest water productivity observed (0.28–0.62 kg m −3 ), relative to a reported global range of 0.6 to 1.7 kg m −3, indicates opportunity to improve wheat water productivity through management and genetic gain.